Year 2000 Grolier multimedia encyclopedia (Danbury : Grolier Interactive, 1999)
Contains 59,000 articles, 15,000 images, 250,000 word dictionary
System requirements: Windows 98, 95, NT Workstation 4.0, 486 DX/100 MHz or higher, 16 MB of memory, 10 MB free hard-disk space
Keywords: Encyclopedia and dictionaries -- Databases